Establishment of chronic Strongyloides ratti infection model and its diagnostic significance - Noor Abdulhaleem; Younis, Hind; Al-Zihiry, Khalid Jameel Kadhim; Awang Hamat, Rukman; Abd Majid, Roslaini; Than, Leslie Thian Lung; Unyah, Ngah Zasmy (Faculty of Medicine, University of Dhi Qar, 2019)
Infection with Strongyloides stercoralis is associated with asymptomatic chronic disease involving the gut and respiratory systems and can persist for long period undetected leading to development of fatal hyperinfection syndrome. The severity is even more in immunocompromised individuals or patients undergoing immune suppressive therapy. Unfortunately the disease is difficult to diagnose due to low parasite load and the irregular larval output. Development of efficient diagnostic techniques requires large supply of infective larvae and this can be achieved through in vivo maintenance of the parasite. In this regard, S. ratti is being used as a model instead of S. stercoralis due to difficulty and risk of infection. In this study, a significant amount of previously characterized filariform (iL3) larvae of S. ratti was collected. Chronic infection was successfully established and maintained by experimentally induced immunosuppression of Wistar rats following oral administration of prednisolone. This model can serve as a good source of infective larvae for production of monoclonal antibodies and development of diagnostic assays for prevention of the disease. It can also provide room for further research in diagnostics of human strongyloidiasis.